Nursing in intensive therapy unit: attention to patients with psychiatric symptoms - Nara Reisdorfer; Leila Mariza Hildebrandt; Marinês Tambara Leite; Luiz Anildo Anacleto da Silva; Mônica Strapazzon (Universidade Federal de Santa Maria, 2018)
Aim: to know the interventions performed by the nursing team in two intensive care units along with patients with psychiatric symptomatology. Method: qualitative and descriptive. Twenty-eight members of the nursing team participated. The data were obtained through a semistructured interview and a non-participant structured observation. The analysis followed the steps of Content Analysis. Results: three categories emerged; the first one refers to dialogue as an instrument of care; the second addresses issues related to mechanical / medication containment; and the last one refers to the family as a therapeutic element in the care of patients with psychiatric symptoms in an intensive care unit (UTI). Conclusion: ICU patients may present psychiatric symptoms due to organic disease or emotional exhaustion due to their presence in such environment. Thus, the intensive care team must be able to identify and intervene assertively with the patient, which includes dialogue and medication administration.